2002
DOI: 10.1186/1471-2156-3-41
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of the COP9/signalosome in budding yeast

Abstract: Background: The COP9/signalosome (CSN), a multiprotein complex consisting of eight subunits, is implicated in a wide variety of regulatory processes including cell cycle control, signal transduction, transcriptional activation, and plant photomorphogenesis. Some of these functions have been linked to CSN-associated enzymes, including kinases and an activity that removes the ubiquitin-like protein NEDD8/Rub1p from the cullin subunit of E3 ligases. CSN is highly conserved across species from fission yeast to hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 36 publications
1
26
0
1
Order By: Relevance
“…Deletions of csn5, csn9, csn10, pci8/csn11 or csi1 bring about accumulation of Rub1-modified Cdc53/cullin, confirming that the CSN partakes in cullin modification in budding yeast ( Figure 3A). While this paper was under review, these results were independently confirmed (Wee et al, 2002), and evidence that Csn5/Rri1 is the catalytic subunit was demonstrated (Cope et al, 2002). Interestingly, Cdc53 modification is insignificantly altered in Δcsn12, which promotes complex disassociation, indicating that integrity of the entire complex is not essential for this hydrolase activity ( Figure 3A).…”
Section: Scientific Reportmentioning
confidence: 63%
“…Deletions of csn5, csn9, csn10, pci8/csn11 or csi1 bring about accumulation of Rub1-modified Cdc53/cullin, confirming that the CSN partakes in cullin modification in budding yeast ( Figure 3A). While this paper was under review, these results were independently confirmed (Wee et al, 2002), and evidence that Csn5/Rri1 is the catalytic subunit was demonstrated (Cope et al, 2002). Interestingly, Cdc53 modification is insignificantly altered in Δcsn12, which promotes complex disassociation, indicating that integrity of the entire complex is not essential for this hydrolase activity ( Figure 3A).…”
Section: Scientific Reportmentioning
confidence: 63%
“…Why this depends on CSN1 and CSN2 but not on CSN3 and CSN4 is still not clear. In contrast to S. pombe, there is no delay in S phase in the budding yeast S. cerevisiae after CSN subunit deletion nor are mutants hypersensitive to UV [4]. However, homologs of CSN1 or CSN2 are not clearly identifiable in these species [4] and levels of overall sequence identity between subunits from budding yeast and those from other organisms are extremely low [27].…”
Section: Introductionmentioning
confidence: 91%
“…2B). The putative yeast CSN5 counterpart, Rri1p (Wee et al, 2002), exhibits only 20% identities (not shown). The gene was named csnE csnD:gfp wild-type Fig.…”
Section: Deletion Of the Csnd Gene Blocks Sexual Development And Causmentioning
confidence: 99%